PELATIHAN MENULIS CERITA UNTUK MENINGKATKAN PRESTASI BELAJAR BAGI ANAK YATIM PIATU DI YAYASAN MATA HATI NOER SALAMAH – GUNUNG KIDUL - Feb Amni Hayati; Ana Septia Rahman; R. Chepi Safei Jumhana (Jurnal Pengabdian Dharma Laksana, 2018)
ABSTRACT This paper aims to find out the extent to which improve learning achievement through writing a story for orphans Yayasan Mata Hati Noer Salamah – Gunung Kidul through training conducted by Pamulang University Lecturer.Approach technique is done by method of seminar and simulation orally and conducted question and answer.Activity results can improve the ability of participants to write stories to improve learning achievement Keywords: Writing, Learning Achievement